(3GdESYGO TQM GdEQTGO (B( (3aj aQhY GdTGaYjg (B)s - (3ceGd GdOjf eMeO Hf CHi HcQ Hf Ydj Hf CHi TQja GdTGaYjs; (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s ((3bGSe Hf eMeO Hf eMeO s)
(3ChdgG (B:s
(3HGH ai GdLQGM GdbJd HZjQ Mb CcHQ GdcHGFQ HYO GdcaQ s
(3BNQgG (B:s
(3dh hWF GfSGf eMQeg GdeedhcI UGQJ eSJhdOI hGdhdO MQfSjH hdReg GdJbQjQ hGddg SHMGfg CYde s
(3Hg WeSs
(3Ydjg Jedc ai Chdgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdTjN eMeO YHO Gddg Bd YHO GdbGOQ GdCfUGQi GdNGUI HGdeHQR (B/ (3GdCMSGA s
Keywords: (3CUhd Gdabgs